Effect of abrupt and frequent changes in forage quality on digestibility and performance of crossbred cattle offered Napier grass (Pennisetum purpureum) and barley straw - Sanda, I.; Romney, Dannie L.; Tauner, J.; Thorne, Peter J.; Leaver, J.D. (British Society of Animal Science, 1999)
Seasonal variation in feed supply, is recognised as an important constraint to animal production in the tropics. However, day to day fluctuations in quantity and quality of feed are also common in stall-fed animals on smallholder dairy farms. Opportunistic use of feeds available in small amounts, such as residues from food crops, weeds and purchased fodder is common. In addition, amounts of cut green fodder may be reduced or absent on some days. Ruminant animals require time to adapt to a given feed and it might be expected that frequent and abrupt changes of this type might have a negative effect on feed utilisation and animal performance. The objective of the experiment was to determine wheather the way in which two fodders, with significantly different DM, CP and fibre contents, were offered, would influence digestibility and liveweight gain in cross-bred cattle.